EFEKTIVITAS EKSTRAK DAUN SALAM (Eugenia polyantha) MENURUNKAN KADAR MALONDIALDEHYDE PADA KONDISI TIKUS HIPERLIPID - Tania, Putu Oky Ari; Cahyadi, I Kadek Angga Dwi (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
A high-fat diet leads to increasing intake of fatty acid in liver, making it susceptible to lipid peroxidation and free radical release. Malondialdehyde is a common biomarker for lipid peroxidation. Increasing free radicals should be balanced with the antioxidants in order to prevent oxidative stress. This study aim was to measured the effectiveness of bay leaf extract (Eugenia polyantha) in lowering MDA levels in hyperlipidemia rats. This study was an experimental study using 20 male rats divided into 4 groups. All rats were induced hyperlipidemia with high-fat diet for 12 days. KP was sacrificed in the next day after the feeding of high fat. KN administered by aquades 2 ml / day (peroral / po), P1 administered by bay leaves extract 1.08 g / day (p.0) and P2 received simvastatin treatment dose 0,0018 g / 150 g BB / day (p. 0). The results showed MDA levels in KP, KN, P1 and P2 were respectively 7.79; 7.07; 6.49; and 7.21 nmol / ml. One way ANOVA test showed p value was 0,073 (